Error Estimates for a Simplified Reissner Theory of Plate Bending - Z. Rychter (Engineering Transactions, 1988)
A simplified Reissner theory for plate bending is dealt with in which transverse displacement occurs as the single unknown variable. The two-dimensional theory used in conjunction with the plane stress theory serves to construct three-dimensional fields whose relative mean square error, under so-called „regular" edge conditions, is shown to be of order of the plate thickness cubed with respect to elasticity solutions.